Synthesis, characterization and adsorption behaviors of Faujasite-type zeolites towards methylene blue. (August 2019) - Zhang, Yunhui; Wang, Zhongwei; Zhang, Zhenguang; Wu, Liuming; Fan, Yingju; Sun, Zhongxi
Abstract: The conventional hydrothermal method was applied to synthesize two microporous Faujasite-type zeolite (FAU) with model substances (sodium silicate, sodium hydroxide and aluminium). The chemical formula of FAU-1 and FAU-2 were 0.99Na2 O·Al2 O3 ·4.07SiO2 ·5.7H2 O and 1.03Na2 O·Al2 O3 ·3.8SiO2 ·8H2 O, respectively. The isoelectric points (IEP) were around 4.5, and the surface area were 244.50 m 2 /g and 485.85 m 2 /g. The adsorption kinetics, intra-particle diffusion and isotherms of methylene blue (MB) on two FAUs were reported from batch adsorption tests. The adsorption obeys pseudo-first-order model and reached equilibrium within 80 min. Intra-particle diffusion is the rate-determining step and the removal decreased with the increase of pH. The adsorption follows BET model, indicating multi-molecular layer adsorption. The adsorption capacity of FAU-2 towards MB is 147.19 mg/g, more than doubles that of FAU-1 (62.74 mg/g). Adsorption mechanism may include ion exchange, hydrogen bonding and hydrophobic interactions. This study may provide guidance for the hydrothermal synthesis of FAU and the universal theoretical basis for its practical application in MB contaminated wastewater treatment.